Differential Evolution in Problems Optimal Parameters Search for Population-Migration Models - Olga Druzhinina; Olga Masina; Irina Vasilyeva (Современные информационные технологии и IT-образование)
The use of computer methods, methods of intellectual analysis and optimization methods for the study of population dynamic models with migration flows is an urgent direction. The use of these methods makes it possible to model complex processes and systems, the study of which by analytical methods is difficult. In this paper, the issues related to the application of the differential evolution method in the problems of modeling population-migration dynamic systems are considered. The population model "two competitors – one migration area" and its modifications are studied. The modeling of the processes of interaction of species in conditions of competition and migration flows is carried out. A series of computer experiments are performed, trajectory dynamics is studied, projections of phase portraits are constructed, qualitative effects are identified and a comparative analysis of the obtained results for such modifications of the "two competitors – one migration area" model, which are associated with variability in the coefficients of natural reproduction of species, intraspecific and interspecific competition, and migration rates. The obtained results can be used in solving problems of global parametric optimization, computer modeling of multidimensional ecological systems, as well as problems of predicting behavior in chemical kinetics systems, and in describing demographic processes.